Variability of (functional) hemodynamics as measured with simultaneous fNIRS and fMRI during intertemporal choice - Heinzel, Sebastian; Häußinger, Florian Benedikt; Hahn, Tim; Ehlis, Ann-Christine; Plichta, Michael M.; Fallgatter, Andreas J. (NeuroImage, 2013)
Neural processing inferred from hemodynamic responses measured with functional near infrared spectroscopy (fNIRS) may be confounded with individual anatomical or systemic physiological sources of variance. This may hamper the validity of fNIRS signal interpretations and associations between individual traits and brain activation, such as the link between impulsivity-related personality traits and decreased prefrontal cognitive control during reward-based decision making. Hemodynamic responses elicited by an intertemporal choice reward task in 20 healthy subjects were investigated for multimodal correlations of simultaneous fNIRS-fMRI and for an impact of anatomy and scalp fMRI signal fluctuations on fNIRS signals. Moreover, correlations of prefrontal activation with trait “sensitivity to reward” (SR) were investigated for differences between methods. While showing substantial individual variability, temporal fNIRS-fMRI correlations increased with the activation, which both methods consistently detected within right inferior/middle frontal gyrus. Here, up to 41% of fNIRS channel activation variance was explained by individual gray matter volume simulated to be reached by near-infrared light, and up to 20% by scalp-cortex distance. Extracranial fMRI and fNIRS time series showed significant temporal correlations in the temple region. SR was negatively correlated with fMRI but not fNIRS activation elicited by immediate rewards of choice within right inferior/middle frontal gyrus. Higher SR increased the correlation between extracranial fMRI and fNIRS signals and decreased fNIRS-fMRI correlations. Task-related fNIRS signals might be impacted by regionally and individually weighted sources of anatomical and systemic physiological error variance. Trait-activation correlations might be affected or biased by systemic physiological responses, which should be accounted for in future fNIRS studies of interindividual differences.